Some European policies regarding acoustical comfort in educational buildings - Vallet, M; Karabiber, Z (INST NOISE CONTROL ENGINEERING, 2002)
Human learning depends strongly on verbal learning. Research has shown that the quality of the acoustical environment is a significant element that influences verbal learning. Noise and room acoustical peculiarities are the main descriptors of acoustical comfort pertaining to learning spaces. The adverse effects of inappropriate acoustical environments on the learning-teaching activities in educational buildings have been summarized by an abundance of research and other published data. Recommendations for both interior noise levels and equipment noise in school classrooms have been documented in a variety of national and international noise policies, guidelines, standards, and regulations. However the importance given to the subject, the content and the context of the requirements depends basically on the general noise policies of the countries involved. This article presents and compares, to a reasonable extent, the acoustical requirements for educational buildings of some European countries. National guidelines, recommendations, regulations and standards are the basic documents referred to in this study. (C) 2002 Institute of Noise Control Engineering.
Keywords: Acoustics; Engineering